COLLABORATIVE LEADERSHIP MODEL IN ACADEMIC GOVERNANCE OF PRIVATE ISLAMIC UNIVERSITIES - Muhammad Alwi; Abdul Halik; Muhammad Tasbih (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze collaborative leadership practices and formulate a leadership model developed within the academic governance of Sekolah Tinggi Agama Islam Darud Da’wah wal Irsyad (STAI DDI) Pinrang. The study employed a qualitative approach with a single-case study design. Informants were selected purposively and included institutional leaders, academic unit heads, lecturers, administrative staff, and other institutional actors involved in academic decision-making. Data were collected through semi-structured interviews, non-participant observations, and document analysis. Data analysis is carried out interactively through the stages of data condensation, data presentation, conclusion drawn, and verification, while data validity is carried out through triangulation of sources and techniques as well as member checking. The findings reveal that the collaborative leadership model at STAI DDI Pinrang is constructed through the integration of four main dimensions: facilitative and relational leadership, participatory academic decision-making, the internalization of prophetic values and ethical role modelling, and strengthened accountability through continuous evaluation and internal quality assurance. The model was not formally or normatively designed but emerged contextually through leadership practices that reduced hierarchical distance, built trust, expanded stakeholder participation, and fostered collective responsibility. The integration of these dimensions resulted in academic governance that was more collaborative, accountable, adaptive, and oriented toward continuous improvement. This study proposes a prophetic value-based collaborative leadership model that may serve as a relevant framework for strengthening academic governance in private Islamic higher education institutions.